Astroglial heterogeneity: merely a neurobiological question? or an opportunity for neuroprotection and regeneration after brain injury? - Ramos, Alberto Javier (2016)
Fil: Ramos, Alberto Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Biología Celular y Neurociencia "Prof. Eduardo de Robertis". Universidad de Buenos Aires. Facultad de Medicina. Instituto de Biología Celular y Neurociencia; Argentina